Can the social construction of technology be used to explain the perception of social media in Zimbabwe?: Paper presented at 11th Zimbabwe International Research Symposium-16-17 February 2017 - Tsokota, Theo; Mahlangu, Gilbert; Rebanowako, Taurai George; Furusa, Samuel S. (Research Council of Zimbabwe, 2018)
The purpose of this study was to determine whether the Social Construction of Technology theory can be used to explain the perception of social media in Zimbabwe. The researchers commenced by identifying relevant groups that apparently hold essential perceptions about the role of social media in Zimbabwe. The groups include civil societies, politicians and government. The methodology for this study was netnography whereby data were collected from online communities and comments in various online newspapers and social media. The researchers used this methodology because it was believed that there is a high level of truthfulness and disclosure depth in online communities than face-to-face conversations. Data was grouped according to relevant groups and then analysed through thematic analysis informed by the six phases of thematic analysis as proposed by Braun and Clarke. The findings of this study indicate though the study had identified various relevant groups, views of Zimbabweans are polarised as a result only three relevant groups emerged from the results. These groups are pro-government, pro-opposition and pro-business. The researchers concluded that those who regard social media beneficial will accept it as the best technology in the modern society, while those who see it as a destructive technology will resist its adoption and use. Hence, technology is not only evolving over time and space to solve problems, but also to cause different perceptions within competing groups. Therefore, the study recommends that there should be education on the proper use of social media. This will remove the fears of the government and there will be closure. As a result, there will be dialogue between the competing groups